2017
DOI: 10.1038/ctg.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Preoperative and Postoperative Plasma Levels of Ghrelin in Gastric Cancer: 3-Year Survival Study

Abstract: OBJECTIVES:We aimed to investigate prognostic effects of plasma levels of ghrelin before and after gastrectomy in gastric cancer (GC).METHODS:We followed 81 GC patients up to 3 years in this study. They were candidates for curative gastrectomy with or without neoadjuvant chemotherapy. Plasma levels of total and active ghrelins before and after the operation were assessed. Association of plasma levels of ghrelin with survival were assessed and adjusted for other potential prognostic factors using Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
(59 reference statements)
1
9
0
Order By: Relevance
“…Such clinical evidence further supports potential indications of aprotinin as an antitumor drug. Similar to other recently introduced agents with potential antitumor effects, 34,35 aprotinin could be considered as an adjunct therapy to complement current chemotherapeutic regimens. In addition to enhancing the efficacy, this combination could decrease the dose of chemotherapeutic drugs needed and limit exposure to their numerous unfavorable toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Such clinical evidence further supports potential indications of aprotinin as an antitumor drug. Similar to other recently introduced agents with potential antitumor effects, 34,35 aprotinin could be considered as an adjunct therapy to complement current chemotherapeutic regimens. In addition to enhancing the efficacy, this combination could decrease the dose of chemotherapeutic drugs needed and limit exposure to their numerous unfavorable toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Authors suggested plasma ghrelin in GC is influenced by the extent of the tumor and H. pylori-induced atrophic gastritis. Plasma ghrelin drops significantly after total gastrectomy (50, 65), showing the stomach as the main source of ghrelin. Blood ghrelin recovered to some extent thereafter, suggesting compensatory production of ghrelin from other non-gastric organs (65).…”
Section: Gastric Cancermentioning
confidence: 99%
“…Higher post-operative plasma ghrelin was linked with better prognosis in GC patients (Table 2; Supplementary Table 3) (50, 105). This survival advantage was independent of stage, grade, cachexia, and tumor size or location.…”
Section: Gastric Cancermentioning
confidence: 99%
See 2 more Smart Citations